The function and future of the LOICS basins approach in promoting integrated coastal zone & watershed management with an emphasis on developing countries - Jones, Jonelle René (2011)
Dissertação de Mestrado, Gestão da Água e da Costa, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2010